1998
DOI: 10.1021/ic971145i
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Isomerization of MSCN(CDOH)2(CDO)BMe to MNCS(CDOH)2(CDO)BMe (M = Tc, Re). Crystal Structures of TcNCS(CDOH)2(CDO)BMe, ReNCS(CDOH)2(CDO)BMe, and ReSCN(CDOH)2(CDO)BMe

Abstract: The 7-coordinate technetium(III) and rhenium(III) monocapped tris(dioxime) complexes [MX(dioxime) 3 BR] have been prepared in which the seventh ligand, X, is thiocyanate or hydroxide (M ) Tc, Re; R ) Me, Et). Both the N-and S-bound thiocyanate linkage isomers are produced during the syntheses, however, the S-bound complex isomerizes to the N-bound analogue. The synthetic routes employed allowed isolation of sufficient quantities of the technetium and rhenium S-bound isomers to be identified; however, full char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The Re–NCS (2.097 Å) bond is within typical ranges for Re(V) complexes with a coordinated thiocyanate and is on the long end of the reported Re–NCS and Tc–NCS bond distances for Re(III) complexes. 22, 5559 The Re–P (2.424 Å) bond distance is comparable to those observed in other Re(III) complexes. 20, 25, 38, 40, 60, 61 …”
Section: Resultssupporting
confidence: 82%
“…The Re–NCS (2.097 Å) bond is within typical ranges for Re(V) complexes with a coordinated thiocyanate and is on the long end of the reported Re–NCS and Tc–NCS bond distances for Re(III) complexes. 22, 5559 The Re–P (2.424 Å) bond distance is comparable to those observed in other Re(III) complexes. 20, 25, 38, 40, 60, 61 …”
Section: Resultssupporting
confidence: 82%
“…The structural characterization of complexes [M(N 3 )(CDO)(CDOH) 2 B-R] (M = Tc and Re) is difficult because organic azides and heavy metal azide salts tend to be highly heat and shock-sensitive explosives (https://en.wikipedia.org/wiki/Azide). Due to the similarity (isoelectronic) between SCN − and normalN3, it is reasonable to believe that complexes [ 99m Tc(N 3 )(CDO)(CDOH) 2 B-R] would share very similar structures with those of [M(NCS)(CDO)(CDOH) 2 B-Me] (M = Tc and Re), which have been determined by X-ray crystallography [48]. This assumption is completely consistent with the fact that 99m Tc-Teboroxime-NCS and 99m Tc-Teboroxime-N 3 shared almost identical HPLC retention times of under the same chromatographic conditions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Structures of complexes [ 99m TcCl(CDO)(CDOH) 2 B-R] were derived from those of complexes [ReCI(CDO)CDOH) 2 BPh], [TcX(dioxime) 3 B-R] (X = Cl, Br; dioxime = dimethylglyoxime, cyclohexanedione dioxime; R = CH 3 and C 4 H 9 ) and [Tc(NCS) (CDO) (CDOH) 2 BMe] [46-48]. …”
Section: Figurementioning
confidence: 99%
“…In the crystallographic literature many metal complexes with dioximes have been reported. In the case of rhenium compounds there are three crystal structures with coordinated monooximes (Jurisson et al, 1991;Jurisson et al, 1998), while the complexes of Re with dioximes were not reported. Therefore, it seemed an attractive idea to obtain new compounds of rhenium with dioximes.…”
Section: Methodsmentioning
confidence: 99%
“…For the structure of the [ReCl 6 ] 2À ion, see: Takazawa et al (1990); Hołyń ska et al (2007). For structures of rhenium compounds with monooximes, see: Jurisson et al (1991Jurisson et al ( , 1998. For background tointeractions, see: Janiak (2000).…”
Section: Related Literaturementioning
confidence: 99%